KEANEKARAGAMAN JENIS DAN PEMANFAATAN TUMBUHAN OBAT DI HUTAN PENELITIAN BU’AT SO’E, KECAMATAN MOLLO SELATAN, KABUPATEN TIMOR TENGAH SELATAN, PROVINSI NUSA TENGGARA TIMUR - Haba, Fidelina Sulastry; Purnama, Maria M. E.; Mau, Astin Elise (Wana Lestari, 2022)
This research has been carried out in the Bu'at So'e Research Forest, South Mollo District, South Central Timor Regency, East Nusa Tenggara Province in September-October 2021. This study aims to determine the diversity of medicinal plant species, the percentage of parts used by the community. local communities, how to process medicinal plants used by local communities and to know the conservation status of medicinal plants found. The method used in this research is descriptive method. The data in this study were collected through vegetation analysis techniques, direct observation in the field to find types of medicinal plants and documentation, interviews using the snowball sampling method in order to obtain informants and obtain appropriate and accurate data. The results of the study found 29 types of medicinal plants that grow and spread in the Bu'at So'e Research Forest area. The diversity of medicinal plants in the Bu'at So'e Research Forest was classified as moderate (H’= 2,133). The people of the Bu'at So'e Research Forest area have knowledge about the use and processing of plants as medicine. There are 38 types of medicinal plants from 22 families used by the community. The plant parts used were leaves (49%), bark (21%), fruit (12%), seeds (12%) and roots (6%). The processing of plants as medicine is carried out by local people in 19 ways, namely chewed, sprayed, swallowed, attached, scratched, boiled, mixed, burned, eaten, smeared, drunk. bathed, squeezed, dripped, soaked, baked, mashed, ground and rubbed. The conservation status for the plants found were Not Evaluated (NE), Low Risk Least Concern (LC), Endangered (EN) and Vulnerable Vulnerable (VU).